Analysis of seismic reflection data from the Northern Hispaniola margin: Implications for the recent evolution of the Northern Caribbean Plate boundary - A. Oliveira de Sá; S. Leroy; E. d'Acremont; S. Lafuerza; J.L. Granja-Bruña; R. Momplaisir; D. Boisson; L. Watremez; B. Moreno; J. Corbeau (Tectonophysics, 2025)

A multi‐population approach supports common patterns in marine growth and maturation decision in Atlantic salmon ( Salmo salar L.) from southern Europe - Cécile Tréhin; Etienne Rivot; Valentin Santanbien; Rémi Patin; Stephen D. Gregory; Ludivine Lamireau; Frédéric Marchand; William R. C. Beaumont; Luke J. Scott; Robert Hillman; Anne‐Laure Besnard; Pierre‐Yves Boisson; et al. (Journal of Fish Biology, 2024)
This study provides a regional picture of long‐term changes in Atlantic salmon growth at the southern edge of their distribution, using a multi‐population approach spanning 49 years and five populations. We provide empirical evidence of salmon life history being influenced by a combination of common signals in the marine environment and population‐specific signals. We identified an abrupt decline in growth from 1976 and a more recent decline after 2005. As these declines have also been recorded in northern European populations, our study significantly expands a pattern of declining marine growth to include southern European populations, thereby revealing a large‐scale synchrony in marine growth patterns for almost five decades. Growth increments during their sea sojourn were characterized by distinct temporal dynamics. At a coarse temporal resolution, growth during the first winter at sea seemed to gradually improve over the study period. However, the analysis of finer seasonal growth patterns revealed ecological bottlenecks of salmon life histories at sea in time and space. Our study reinforces existing evidence of an impact of early marine growth on maturation decision, with small‐sized individuals at the end of the first summer at sea being more likely to delay maturation. However, each population was characterized by a specific probabilistic maturation reaction norm, and a local component of growth at sea in which some populations have better growth in some years might further amplify differences in maturation rate. Differences between populations were smaller than those between sexes, suggesting that the sex‐specific growth threshold for maturation is a well‐conserved evolutionary phenomenon in salmon. Finally, our results illustrate that although most of the gain in length occurs during the first summer at sea, the temporal variability in body length at return is buffered against the decrease in post‐smolt growth conditions. The intricate combination of growth over successive seasons, and its interplay with the maturation decision, could be regulating body length by maintaining diversity in early growth trajectories, life histories, and the composition of salmon populations.

Prior cortical activity differences during an action observation plus motor imagery task related to motor adaptation performance of a coordinated multi-limb complex task - J. Ignacio Serrano; Daniel Muñoz-García; Raúl Ferrer-Peña; Victor D’eudeville; Marta Brero; Maxime Boisson; M. Dolores del Castillo (Cognitive Neurodynamics, 2020)

Targeting VEGFR1 on endothelial progenitors modulates their differentiation potential - Clément d’Audigier; Benoit Gautier; Alexis Yon; Jean-Meidi Alili; Coralie L. Guérin; Solène M. Evrard; Anne Godier; Skerdi Haviari; Marie Reille-Serroussi; Florent Huguenot; Blandine Dizier; Nicolas Inguimbert; et al. (Angiogenesis, 2014)

Bioaccumulation of zinc in the scleractinian coral Stylophora pistillata - C. Ferrier-Pagès; F. Houlbrèque; E. Wyse; C. Richard; D. Allemand; F. Boisson (Coral Reefs, 2005)

Characterisation of Coagulase-Negative Staphylococci Isolated from Blood Infections: Incidence, Susceptibility to Glycopeptides, and Molecular Epidemiology - Boisson K.; Thouverez M.; Talon D.; Bertrand X. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)